Squirm - Hiaasen, Carl (Alfred A. Knopf, 2018)
Billy Dickens discovers that his mysterious father lives in Montana, so this summer Billy will fly across the country, hike a mountain, float a river, dodge a grizzly bear, shoot down a spy drone, and save his own father.